Estudo da Similaridade Genética de Amostras de Acinetobacter baumannii Produtoras de Carbapenemases do Tipo OXA Isoladas em Diversos Hospitais Brasileiros - Werneck, Jessica Sanchez de Freitas [UNIFESP] (2010)
In this dissertation we present two studies involving carbapenem-resistant Acinetobacter baumannii clinical isolates due to the production of carbapenems modifying enzymes, the OXA-type carbapenemases. The first study aimed to determine the genetic relationship of multi-drug-resistant A. baumannii producing OXA-23 that was isolated in distinct Brazilian cities. A total of 91 A. baumannii clinical isolates were recovered from 17 medical centers located at eight cities, namely São Paulo (SP), Rio de Janeiro (RJ), Belo Horizonte (MG), Porto Alegre (RS), Blumenau (SC), Curitiba (PR), São Luiz (MA) and Salvador (BA). In this collection we observed high rates of carbapenems resistance (91.2%). Also, the blaOXA- 23-like gene was present in 83.5% of isolates. The insertion sequence ISAba1 was positioned upstream the blaOXA-23 gene in all OXA-23-producing A. baumannii identified. Nine clusters were observed among OXA-23 producers. Our fidings suggest that the blaOXA-23 gene was probably chromosomally-located in all isolates studied. Three clusters (A, B and D) were found in six cities from southeast and southern reagions of Brazil. In addition, the predominant cluster (A) was clonally related to that first described in Curitiba, in2003. In contrast, a single cluster of A. baumannii producing OXA-23 was found in São Luís city. Although there were previous reports regarding the spread of OXA-23-producing A. baumannii in Brazil the following features had not yet been assessed: i) the comparative analysis of OXA-23 producers genotypes originating in distinct and distant Brazilian cities, ii) the genetic location of the blaOXA-23 gene and iii) the presence of ISAba1 upstream blaOXA-23 probably resulting in high degree of carbapenem resistance. Thus, our study demonstrates that the clonal dissemination of OXA-23- producing A. baumannii had occurred in Brazil. These findings emphasize that infection control measures are urgently needed to reduce both the spread of multidrug resistantstrains and the number of infections caused by this pathogen. The second study refers to a case report involving a hospitalized patient that presented an wound infection due to OXA-72-producing A. baumannii. The referred clinical isolate, A 30235, was resistant to most antibiotics tested and showed reduced susctptibility to ampicillin/sulbactam. Successful transformation assays using A. baumannii ATCC 19606 as the recipient strain revealed the plasmid location of the blaOXA-72 gene. This plasmid showed molecular weight of about 86 Kb. We identified for the first time in Brazil, an A. baumannii clinical isolate producing OXA-72. The presence of this resistance determinant encoded by a gene located in a mobile genetic elemet, points out to an increasing diversity of OXA-type carbapenemase in Brazil with potential spread. Appropriate control measures should be taken to prevent the spread of OXA-72 producers among Brazilian hospitals, which it we have experienced with OXA-23- producing-A. baumannii in this country.